Media configuration and recirculation of upflow anaerobic floating filter for piggery wastewater treatment - Lee, S.; Lee, H.; Lee, S.; Chitapornpan, S.; Chiemchaisri, C.; Polprasert, C.; Ahn, K. (Springer New York, 2007)
An upflow anaerobic floating filter media (UAFF) reactor was applied to the treatment of synthetic and real piggery wastewater. The effect of media configuration and internal recirculation on the system performance was studied. In the first experiment, three-UAFF reactors filled with different media, i.e., polypropylene beads, sponge cubes and coconut fiber were continuously fed with synthetic wastewater at upflow velocity of 0.04 m h-1. The COD removal efficiency in the reactor filled with sponge cubes was highest at 90%, whereas the others filled with polypropylene beads and coconut fibers with lower specific surface area were about 80%. In the second experiment, three-UAFF reactors with sponge were applied to treat real piggery wastewater. COD removal efficiencies were found to be about 80% and methane production rate of 0.26 l l r -1 d-1. The system performance could be slightly improved by 10% when applying internal recirculation. A sludge blanket (60-70% of total biomass) plays an important role in the system when applied to the treatment of piggery wastewater containing high suspended solid concentration. ？ 2007 Springer.